Determinants of euro term structure of credit spreads - Astrid Van Landschoot (European Central Bank (ECB), 2004)
In this paper, we investigate the determinants of the Euro term structure of credit spreads. More specifically, we analyze whether the sensitivity of credit spread changes to financial and macroeconomic variables depends on bond characteristics such as rating and maturity. According to the structural models and empirical evidence on credit spreads, we find that changes in the level and the slope of the default-free term structure, the market return, implied volatility, and liquidity risk significantly influence credit spread changes. The effect of these factors strongly depends on bond characteristics, especially the rating and to a lesser extent the maturity. Bonds with lower ratings are more affected by financial and macroeconomic news. Furthermore, we find that liquidity risk significantly increases credit spreads, especially on lower rated bonds.
Keywords: C22; E45; G15; 330; Credit risk; Nelson-Siegel; Structural models